Barefoot vets show their worth - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
In 1987, the first barefoot vets in Kenya were trained by the Intermediate Technology Group in Meru district. Now the area has a total of 80 'wasaidizi wa mifugo' - helpers of livestock. The programme has been copied in other parts of the country,...